1T/2H mixed phase MoS2 in-situ grown on the surface of montmorillonite for selectively removing Pb2+. (June 2022) - Cheng, Y.; Yang, S.; E, Tao; Liu, L.; Wang, D.; Qian, J.
Abstract: Molybdenum disulfide (MoS2 ), as a kind of adsorbent, can selectively remove Pb 2+ from water. However, agglomeration and fewer active S sites are the two factors that spoil the adsorption performance of MoS2 . In order to solve these problems, a new type of adsorbent: 1T/2H mixed-phase MoS2 (D-MoS2 )/montmorillonite composites (D-Mt) are proposed via the one-step hydrothermal method, associated with filling cations. Among them, S defects are intentionally introduced to promote the conversion of the 2H phase in MoS2 into 1T phase, contributing by adding an excessive amount of CH4 N2 S and using the hydrothermal method. Moreover, owing to filling with Na +, D-MoS2 is uniformly dispersed driven by electrostatic force. Consequently, D-Mt has a large density of edge active sites, contributing to a greatly improved adsorption capacity with 175.57 mg/g, which can be attributed to the different growth directions of MoS2 nanosheets and its unique defect structure as well as the inhibited masking effect on –OH that existing on the edge of montmorillonite. Additionally, the adsorption mechanism is confirmed via theoretical calculations, which suggests that there are electron transfers between O 2p, S 3p and Pb 6p, indicating that Pb 2+ could be adsorbed via three paths, including interlayer ion exchange, –OH on the edge as well as S defects in D-Mt. Graphical abstract: Image 1 Highlights: 1T/2H mixed phase molybdenum disulfide (MoS2 ) is in-situ grown on the surface of montmorillonite. More S defects are formed by creating 1T MoS2 and adding excessive CH4N2S. Electrostatic force on the surface of montmorillonite drives D-MoS2 to be uniformly dispersed.